Ancient place names of Greek and Latin origin in the Cilician plain - Alla Linko (Vestnik Pravoslavnogo Svi͡a︡to-Tikhonovskogo gumanitarnogo universiteta. 3, Filologii͡a, 2024)
The ancient toponymy of the Cilician Plain (Asia Minor) has a heterogeneous character, a significant part of the geographical names are of substrate origin, which reflects the rich ethnopolitical history of this region. During the Hellenistic era many Greek place names were replaced. The second wave of renaming began after the Roman conquest of Cilicia. Geographical names of ancient Greek and Latin origin were selected and analyzed among the toponyms of the Cilician Plains for morphological structure and lexico-semantic features. Much attention is paid to the problems of etymologization of toponyms, the definition of the basic principles of naming geographical objects and the patterns of renaming. The classification of Cilician toponyms according to chronology is proposed, which identifies the word-formation models of toponyms peculiar to each epoch: appellatives, substantive adjectives, derivatives of personal names, two-part toponyms (compounds and juxtaposed compounds).